Effect of insulin upon the sodium pump in frog skeletal muscle - Moore, Richard D. (1973)
1. Insulin increased the rate of net Na extrusion from Na-loaded frog skeletal muscle into glucose-free Na-Ringer. After a 90 min period of efflux, the insulin-treated muscles contained approximately 11% less intracellular water than did their controls. This decrease in intracellular water resulted in an increase in the concentration of intracellular K, [K(+)](i), even though there was no definite effect upon net K flux. In spite of the decrease in intracellular water, [Na(+)](i) was lower in those muscles treated with 500 m-u. insulin/ml. than in the controls. 2. Insulin consistently increased (22)Na efflux into Na-Ringer containing either 10 or 2·5 mM-K(+). This effect was reversible and was not produced by other proteins. 3. Acetylstrophanthidin (5 × 10(-6) M) blocked all or nearly all net Na efflux even in the presence of insulin. The presence of this concentration of acetylstrophanthidin or of K-free Na-Ringer inhibited the effect of insulin upon (22)Na efflux from Na-loaded muscles. 4. All of the above results indicate that insulin in some way increases the activity of the Na pump. The inhibition by K-free Na-Ringer also suggests that this is not due to production of additional pump sites. 5. Insulin also increased (22)Na efflux and net sodium efflux into Li-Ringer. When the new steady-state was reached after addition of insulin, the (22)Na kinetics still obeyed a power relation to intracellular (22)Na. However, in every single case, insulin resulted in a decrease of approximately 18% in the exponent, n. 6. Curve-fitting of the kinetic data to equations based upon a three-site model of the Na pump suggests that insulin increases the affinity of the sites toward Na(+). In terms of Eisenman's theory of ion selectivity, this would indicate an increase in the anionic field strength of the Na-carrying sites and also predict that the increase in affinity for H(+) would be greater than that for Na(+). This latter prediction is entirely consistent with the observed decrease in n. 7. The results suggest that insulin may be increasing H(+) efflux as well as Na(+) efflux and thereby may be increasing intracellular pH. It is suggested that some of the intracellular effects of insulin might be mediated by such an effect.